การรับรู้ข่าวสารและการยอมรับการใช้ก๊าซของผู้ขับขี่รถยนต์ในเขตกรุงเทพมหานคร - สุพนิตตา สุวรรณสะอาด (จุฬาลงกรณ์มหาวิทยาลัย, 2009)
This research has the objectives to study the access of the energy information and factors related to the decision in order to use gas instead of the driver s oil in Bangkok Metropolitan which are the population nature, the NGV and LPG gas perception. The example is 400 people in Bangkok Metropolitan who are 18 years up and drive with gas (NGV and LPG gas), filling NGV and LPG gas at the NGV and LPG filling station. The data collection tool is questionnaire codified with SPSS program and information analysis with percentage, average and Pearson s Product Moment Correlation Coefficient. The results are:- 1. Drivers with the population nature of different age, income and career have decision to use NGV and LPG differently. For the different gender and education, decision to use NGV and LPG is not different. 2. NGV and LPG energy information access of the example has is not related to the decision to use NGV and LPG. 3. Drivers have the opinion regarding the NGV and LPG no related with comparative advantage. 4. Drivers have the opinion regarding the NGV and LPG related with complicated use. 5. Drivers have the opinion regarding the NGV and LPG no related with noticeable competence. 6. Drivers have the opinion regarding the NGV and LPG related with compatibility